DEVELOPMENT OF HYBRID COAL PRODUCTION PROCESS - Irma
Coal is one of the abundant sources of fossil energy in Indonesia. Until now its use is still one of the main choices, regardless of the use of coal, there are problems, namely the high amount of CO2 emissions, coal is considered an energy source that is not environmentally friendly, so it is necessary to carry out processing that is able to overcome these problems. Meanwhile, biomass waste in Indonesia is very abundant, and it is known that biomass as an environmentally friendly fuel because it has a neutral carbon footprint value, so that if coal and biomass are combined in the co-torefaction process it can produce a new product, namely hydride coal which is has a neutral carbon footprint value than the original coal. This research is a continuation of research on hybrid coal which previously used a rotating drum reactor with a capacity of 1 kg. The purpose of this study was to evaluate the performance of the hybrid coal cotorrefaction process in the rotary drum reactor that occurred during the experimental process, with the specific objective of knowing the results of the reactor performance by modifying the reactor so that the heat generated during the torrefaction process can be more evenly distributed and determine the quality of the resulting hybrid coal products. The reactor operates at atmospheric pressure in which there are two chambers, namely the drum as the co-torofaction chamber and the shell as the combustion chamber. Process variables were varied, namely the feed:fuel ratio and the feeding process with a ratio of 1:3, 1:4, and 1:5. The energy source uses biomass heat, sub-bituminous coal and pine sawdust with a mixture composition of 30%. The development of hybrid coal production is capable of producing a calorific value of 6947-7959 cal/g with energy and mass gains, namely in the range of 77- 86% and 78.63-89.20%. The mass and energy gains have decreased from previous studies because the fuel was overloaded in the combustion chamber, requiring further study on the intermittent fuel feeding process. With this research, it is hoped that it can provide answers about a good system to meet energy needs in the manufacture of hybrid coal which can later be applied on a larger scale in the industry and be able to compete with raw coal as a start towards environmentally friendly technology.